Patterns of Theoretical Similarity - Kara L. Vander Linden (Grounded Theory Review: An International Journal, 2017)
Classic grounded theories explicate patterns of behavior used by individuals within a substantive area to address problematic areas that they are working to address. Through the brief examination and explanation of two classic grounded theories conducted by the author, overlapping patterns of theoretical similarity are discussed despite the theories’ emergence from different substantive areas. The future development of formal grounded theories from these and other substantive grounded theories is discussed.